Use of Project-Based Learning Model in Arabic Language Learning to Improve Students' Listening and Reading Skills - Sholihah, Hilda Jamilatu; Mohammed Ali, Sabri (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
This study explores the effectiveness of a project-based learning model in Arabic language teaching to improve students' listening and reading skills, aiming to determine if this approach yields better results than traditional methods. A quasi-experimental design with pre-tests and post-tests was conducted with control and experimental groups of Class XI B students. Before the intervention, students' listening and reading skills scored averages of 67 and 66, respectively, indicating moderate proficiency. The project-based approach incorporated information and communication technology topics, finding synonyms, listening to recordings, and watching instructional videos. This approach was designed to make learning more engaging and contextually relevant. After implementing the project-based learning model, students in the experimental group showed significant improvement: listening skills rose to an average score of 81, while reading skills increased to 80. This represented effect sizes of 41% and 45%, respectively, highlighting the model's positive impact on skill enhancement. Integrating project-based learning into Arabic language curricula at the secondary level is recommended to enhance student engagement and comprehension, particularly in complex subjects. Using relevant themes like technology may further contextualize learning and improve outcomes. Future research should investigate this model's long-term impact and adaptability across different proficiency levels and educational contexts, supporting a more engaging and effective approach to Arabic language instruction.